Association of nNOS Gene Polymorphism with Ischemic Stroke in Han Chinese of North China - Yingjie Dai; Zhiyi He; Rubo Sui; Zhilin Jiang; Shanshan Ma (The Scientific World Journal)
Nitric oxide (NO) is an important messenger molecule and effector molecule. This study aimed to investigate the relation of neuronal nitric oxide synthase (nNOS) gene polymorphism with ischemic stroke in Han Chinese of North China. This was a case-control study. A total of 413 patients with ischemic stroke were recruited from Han Chinese of North China. There were 201 males and 212 females. In addition, 477 healthy subjects served as controls including 224 males and 253 females. Multiplex SNaPshot was employed to detect nNOS gene polymorphism (rs2293050, rs2139733, rs7308402, and rs1483757). Results showed that the rs1483757, rs2139733, and rs2293050 genotypes and allele frequencies were comparable between patients and controls. However, ischemic stroke patients had significantly reduced AG genotype and A allele frequency when compared with controls (P=0.037, P=0.041). After adjusting confounding factors (gender, age, smoking, history of drinking, hypertension, and diabetes), AG genotype and A allele were still related to ischemic stroke (OR=0.572, 95% CI: 0.335–0.978, P=0.041; OR=0.611, 95% C: 0.378–0.985, and P=0.041) and both were found to be protective factors. Our results showed that rs7308402 gene polymorphism of nNOS is related to ischemic stroke in Han Chinese of North China.